Peran Forum Anak Desa Talawi Hilie (Fatih) Sebagai Pelopor Dan Pelapor Dalam Pemenuhan Hak-Hak - Lisa Putriani; Mohamad Allzis; Arifin Ilham; Juan Riski Setiawan; Clara Purti Fadilla; Tengku Sakinah Handriah (CV. ITTC INDONESIA, 2025)
The Forum Anak Desa Talawi Hilie (FATIH) is a child participation platform at the village level aimed at ensuring the fulfillment of children’s rights and providing space for children to act as pioneers and reporters (2P) in village development. This activity aims to explore the roles, challenges, and contributions of FATIH in realizing a child-friendly village. The method used in this activity is a qualitative approach through direct interviews with the FATIH mentor. This approach was chosen to obtain in-depth and contextual information about the forum’s activities, the support it receives, and the mentor’s perspective on children’s participation in the village. The results of this activity indicate that FATIH has been actively implementing various programs that support child protection and empower children as agents of change. However, continuous support from the village government, the community, and related stakeholders is still needed to optimize the role of the child forum.